2022
DOI: 10.3389/fmicb.2022.903363
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Exopolysaccharide From Newly Isolated Marine Probiotic Lactiplantibacillus plantarum EI6 With in vitro Wound Healing Activity

Abstract: Because of its safety, biological activities, and unique properties, exopolysaccharide (EPS) from lactic acid bacteria (LAB) has been developed as a potential biopolymer. A few studies have investigated the EPS produced by marine LAB. This study reports the wound healing activity of an EPS produced by a marine isolate identified as Lactiplantibacillus plantarum EI6, in addition to assessing L. plantarum EI6's probiotic properties. EI6 demonstrated promising antimicrobial activity against different pathogenic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 75 publications
0
14
0
3
Order By: Relevance
“…In addition, EPS has shown to mitigate experimental colitis, improving mucosal barrier function, and modulating gut microbiota composition ( 80 82 ). Moreover, recent studies have suggested that applying EPS from lactic acid bacteria to the skin enhances skin health and proven to be aid in gastrointestinal wound healing in different in-vitro and in-vivo studies ( 83 , 84 ). It would be advantageous to consider EPS as a feasible prebiotic choice for therapeutic purposes due to its two feathers: EPS is indigestibility to the host cells, thus, arriving in the colon intact and consumed by specific gut microbiota in the colon ( 85 ).…”
Section: Commensal Bacterium-derived Factors Promote Intestinal Epith...mentioning
confidence: 99%
“…In addition, EPS has shown to mitigate experimental colitis, improving mucosal barrier function, and modulating gut microbiota composition ( 80 82 ). Moreover, recent studies have suggested that applying EPS from lactic acid bacteria to the skin enhances skin health and proven to be aid in gastrointestinal wound healing in different in-vitro and in-vivo studies ( 83 , 84 ). It would be advantageous to consider EPS as a feasible prebiotic choice for therapeutic purposes due to its two feathers: EPS is indigestibility to the host cells, thus, arriving in the colon intact and consumed by specific gut microbiota in the colon ( 85 ).…”
Section: Commensal Bacterium-derived Factors Promote Intestinal Epith...mentioning
confidence: 99%
“…The chemical composition analysis ascertained that the REPS sample possessed a considerable amount of carbohydrates. The former studies have found that LAB-EPS has high carbohydrate content (Li et al 2014 ; Wang et al 2015 ; Imran et al 2016 ; Zaghloul and Ibrahim 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of L. rhamnosus GG and L. gasseri , for instance, is thought to hasten the healing of stomach ulcers in rats. Probiotics have been shown to assist in the healing of gastric wounds, so researchers have begun to investigate whether they might also aid in the healing of cutaneous wounds (Sultana et al 2013 ; Zaghloul and Ibrahim 2022 ). At the same time, derivatives of probiotics such as polysaccharides may be more suitable candidates for the development of effective and non-toxic wound healing agents with stronger activities (Ammar et al 2015 ) to overcome obstacles related to maintaining the viability of living cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cilt dışardan vücuda girecek olan patojenlere karşı ilk bariyer görevini üstlenen ,termoregülatör işlev gören ve immünolojik süreçlere katılan önemli bir yapıdır [135]. Cildin mikrobiyotası sağlığını ve homeostasını korur [135]; ancak fiziksel ya da kimyasal yanıklar, bağ dokusu bozuklukları, diyabet gibi metabolik hastalıklar,iltihaplanma, ameliyat gibi yaralanmalarla bu homeostas değişir [135,136]. Her nekadar sağlıklı insanlarda yaraların iyileşme süreci birkaç günü alsada diyabet hastalarında olduğu gibi bazı yaraların iyileşmesi daha uzun sürer veya hiç iyileşmez.…”
Section: Eps'nin Yara İyileştirici öZelliğiunclassified
“…Mevcut yaraların çoğu için iyileştirici ilaçlar maliyetlidir ve çeşitli yan etkilere neden olur. Bu nedenle, güvenli, maliyet bakımından düşük ve hastalar tarafından daha iyi tolere edilebilen etkili yara iyileştirme biyoaktif bileşiklerine sürekli bir talep vardır [135]. Yara iyileşmesinin majör fazları; inflamasyon, proliferasyon (granülasyon doku formasyonu) ve remodeling fazları olup bu fazların birbiri ile entegre sürelerde gerçekleştiği bilinmektedir [136].…”
Section: Eps'nin Yara İyileştirici öZelliğiunclassified